(untitled) (Semiárida, 2020)
In this contribution the whole genera and species of the Chenopodiaceae family which grows spontaneously in this province, are listed. This family is represented by 12 genera with 38 species. Keys for the identification of the genera and species are included and a short description of each genus is given. Distribution, origin diffusion in La Pampa and usefulness of each species are given. 25 species are illustrated.